The Role of Smart Cities during the COVID-19 Pandemic – the Example of New York City - Kozak, Alicja (Rola miast inteligentnych w czasie pandemii COVID-19 na przykładzie Nowego Jorku, 2022)
This paper investigates how smart cities responded to the COVID-19 pandemic-related issues based on the example of New York City (the case study formula). The first part of the research constitutes a background to the study. The specific challenges and city responses that the pandemic introduced to urban centres are indicated. The second part contains research on various definitions of the smart city concept. Since there is no official characteristic of such an urban centre, the commonly accepted attributes were indicated in the study. The first and second parts are based on desk research. Finally, in the last phase of the research, a case study analysis of New York City was conducted to present manifestations of previously indicated attributes of a smart city concept. The actions taken by the city authorities and other city actors to address the challenges that were both common for cities and specific ones (that applied to New York City) were investigated.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 23-33
Keywords: COVID-19; pandemic; smart city; New York; panedemia; miasto inteligentne; Nowy Jork